STUDI KEPUSTAKAAN: KEAMANAN INFORMASI DI PERPUSTAKAAN DIGITAL - Asyifa Putri Triandari (Perpustakaan Nasional RI, 2022)
Are all the information stored in digital libraries, both information in the form of collections or user personal data, guaranteed security? This article discusses the threats to information security in digital libraries and their prevention. This study uses a qualitative method with a research library technique, namely research that refers to previous studies, several expert opinions, and other reliable sources obtained by the author by digitally reviewing the research results. The research conducted shows that information security threats in digital libraries do not attack programs or applications that are used to manage information only, but also physical objects to store the information. Examples of information security threats to digital libraries are malware which consists of various types. The easiest way to keep information that is stored safely is by backing up (duplicating information). However, backup alone is not enough. It is necessary to improve the performance of librarians or other training managers by including various national and international events. Not only human resources, but various devices used in digital libraries also need to be updated so that the system that is run is not easily disturbed. In addition, digital libraries should in some time hold simulations of conceding information, so that when such unexpected incidents occur, libraries can take appropriate steps so that the impact that occurs is not more widespread.